AWARENESS ON ORAL HYGIENE PRACTICES AMONG RURAL PRIMARY SCHOOL TEACHERS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2025)
Oral disease can be viewed as a general medical issue because of its high pervasiveness and huge social effect. Interminable oral ailment ordinarily prompts tooth loss, and has physical, psychological and monetary impact. This survey was done to assess the awareness on oral hygiene practices among rural primary school teachers. A closed ended questionnaire, consisting of 10 components, was distributed among rural primary school teachers in the Madurai district of Tamil Nadu , India (n=127).The questionnaire elicited knowledge and practices of oral hygiene, their brushing habits, use of tooth paste, powder, use of mouth rinses, practice of night brushing and tongue cleaning. The responses were collected and analysed. 100% of the respondents practice regular tooth brushing.42% of them brushed both during the morning and night and 58% brushed in the morning,96% used tooth paste and 4% used tooth powder.34% used mouth rinses.16% used tongue cleaners. The findings of the study indicated that the awareness and knowledge of oral hygiene among primary school teachers in the rural district of Salem was good. Teachers, nevertheless, need educational programs ,workshops and symposiums on oral health issues to further empower them to educate the students